The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/bre.12408
|View full text |Cite
|
Sign up to set email alerts
|

Late Miocene evaporite geochemistry of Lorca and Fortuna basins (Eastern Betics, SE Spain): Evidence of restriction and continentalization

Abstract: The Lorca and Fortuna basins are two intramontane Neogene basins located in the eastern Betic Cordillera (SE Spain). During the Late Tortonian-Early Messinian, marine and continental evaporites precipitated in these basins as a consequence of increased marine restriction and isolation. Here we show a stratigraphic correlation between the evaporite records of these basins based on geochemical indicators. We use SO 4 isotope compositions and Sr isotopic ratios in gypsum, and halite Br contents to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…The overlying pink marls and sandstones correspond to the Post-evaporitic unit attributed to the Messinian by Wrobel and Michalzik (1999). However, Rouchy et al (1998) and Garcia-Veigas et al (2019) only found reworked foraminifera and non-marine biostratigraphical markers, which did not allow them to determine the age of the formation.…”
Section: Lithostratigraphical Frameworkmentioning
confidence: 96%
See 4 more Smart Citations
“…The overlying pink marls and sandstones correspond to the Post-evaporitic unit attributed to the Messinian by Wrobel and Michalzik (1999). However, Rouchy et al (1998) and Garcia-Veigas et al (2019) only found reworked foraminifera and non-marine biostratigraphical markers, which did not allow them to determine the age of the formation.…”
Section: Lithostratigraphical Frameworkmentioning
confidence: 96%
“…All these authors proposed a Messinian age for these evaporites, while Krijgsman et al (2000) considered a Tortonian age. A Tortonian age was also proposed by Garcia-Veigas et al (2019) on the basis of ages proposed by Corbi et al (2012) themselves based on ages proposed by Krijgsman et al (2000). The overlying pink marls and sandstones correspond to the Post-evaporitic unit attributed to the Messinian by Wrobel and Michalzik (1999).…”
Section: Lithostratigraphical Frameworkmentioning
confidence: 96%
See 3 more Smart Citations